Experiences of older patients with cancer from the radiotherapy pathway – A qualitative study. (August 2021) - Volungholen Sollid, May Ingvild; Kirkevold, Øyvind; Slaaen, Marit; Ervik, Bente; Melby, Line; Eilertsen, Grethe
Abstract: Purpose: To explore and describe experiences of older patients with cancer throughout their radiotherapy treatment, from diagnosis until follow-up after treatment. Methods: Individual interviews were conducted to explore different phases of radiotherapy. Interviews were recorded and transcribed verbatim. Inductive content analysis was applied. Each interview was coded separately. Then to the codes were analyzed further, and an overall theme was developed. Results: Twelve older patients with cancer, (7 male, 5 female) aged ≥ 65 related their experiences from radiotherapy treatment. A main theme describes the essence of their experiences; Understanding "just enough" . The theme comprises five main categories: Understandable, adapted information is crucial for trusting health services; Previous experiences influence patients' perception and understanding; Involvement of next of kin is crucial to patients' comprehension; Professional treatment decisions and well-organized treatment determines satisfaction and Experiences of cooperation and coordination of services affects dependability. Conclusions: Findings from this study describe how understanding "just enough" – not too much nor too little – may assist older patients with cancer in participating in treatment decisions, preventing false beliefs, feeling reassured during treatment and in navigating the complex health care system. Next of kin are important assets for older patients with cancer in understanding "just enough". Cancer nurses may map comprehension of information, as well as reveal patients' previous experiences. Highlights: The radiotherapy pathway is experienced as a continuous process. Understandable, adapted information is crucial for trusting health services. Previous experiences influence patients' perception and understanding. Next of kin are important assets for older patients with cancer. How cooperation and coordination of services is experienced affects dependability.